Biological and Ecological Aspects of Freshwater Macrophytes in the Coastal Areas of Bintulu and Miri, Sarawak, Malaysia - Awing, Suzalina Akma (2008)
Freshwater macrophytes were surveyed for their distribution, habitat characteristics and local uses around Bintulu division and Miri district, Sarawak, East Malaysia from year 2004 until 2006. Thirty nine (39) areas were covered where two lakes and five streams of natural and man made water bodies (one marsh, two temporary marshes, four ponds, one disused mining lake and eight ditches) from Bintulu division while from Miri district, one area of stream (natural) and four man made water bodies (two marshes, three ponds, seven ditches and three areas of water reservoirs). A total of 113 species and 42 families of freshwater macrophytes were recorded in various habitats and areas of Bintulu division and Miri district. Fifty five (55) species in 12 families are angiospermae monocotyledon e.g. Limnocharis flava, Eriocaulon longifolium, Cyperus halpan and Blyxa aubertii, 49 species in 24 families are angiospermae dicotyledon e.g. Nelumbo nucifera, Nymphaea nouchali, Ceratophyllum demersum and including seven species in three families of carnivorous plants, Drosera spathulata, Utricularia aurea, U. bifida, U. caerulea, U. gibba, U. minutissima and Nepenthes gracilis. Eight species in six families are categorized as ferns e.g. Salvinia molesta, Nephrolepis bisserata, Lygodium microphyllum and macroalgae, Chara zeylanica. Based on life form categories, three species were emergent (N. nucifera, N. nouchali and N. pubescens), five species as submerse (e.g. C. zeylanica, B. aubertii, Hydrilla verticillata and U. bifida), eight species as floating (e.g. Pistia stratiotes, Ipomoea aquatica, Lemna perpusilla, U. aurea, U. gibba and Eichhornia crassipes) and 99 species as marginal or half-submerse (e.g. L. flava, Ipomoea stolonifera, C. halpan, Eleocharis dulcis, N. bisserata, D. spathulata, U. caerulea and Typha angustifolia). The distribution of freshwater macrophytes e.g. H. verticillata, U. gibba in various natural (e.g. Kemena lake, Jalan Nyabau stream) and man made water bodies (e.g. Taman Mawar pond, UPM Bintulu campus ditch) were not affected by physical environmental factors where the water and substrate were slightly acidic to alkaline, pH ranged 6.79 to 7.82 with water temperature of 25ºC to 34.6ºC. Freshwater macrophytes grew in slightly acidic to alkaline of water and substrates of clay and sandy clay loam. Freshwater macrophytes also grew in water temperature of 24ºC to 38ºC and tolerated up to 40ºC. Species such as C. zeylanica and T. angustifolia grew in water of 5 ppt and N. nouchali were abundantly growing in black colour water with a pH of 5.5 or less. The variations on morphology of vegetative and reproductive structures contribute to their adaptation and survival in a variety of environmental conditions. The arrangement of leaves e.g. rosette in N. nouchali to avoid shading and overlapping of leaves and helps the plant gets more sunlight. The vacuoles in the petioles and rhizomes e.g. N. nucifera function for gas transportation while swollen petioles in certain species e.g. E. crassipes enables the plant to float on water surface. Certain species have “head” inflorescences such as Mimosa pudica that function to avoid overlapping of flowers for easy pollination. The modification of seed structure e.g. “winged” seeds in U. gibba allows buoyancy of seeds for dispersal. Forty three species of freshwater macrophytes are used by the local population. The marginal plants such as Cyperus brevifolius, E. dulcis, Alternanthera sessilis and Homalomena propingua are the sources of most food and medicines. Other than as food and medicine, freshwater macrophytes are also used as an ingredient in making cosmetics (e.g. Melastoma malabathricum), household items e.g. aromatherapy foam bath (e.g. N. nouchali), making mats, baskets and as binding material (Cyperus malaccensis known as “Tali bondong” among local peoples), aquarium and decorative plants (e.g. Cabomba furcata, Monochoria hastata, M. vaginalis, D. spathulata, U. bifida and U. minutissima). Salvinia molesta and L. microphyllum are cultivated by local peoples and used as biofilters and biodegradable plants in water reservoirs.